WINTER CYCLING IN VERY COLD CLIMATE – A CASE STUDY IN CALGARY - Farnaz SADEGHPOUR; Shabtai ISAAC; Mona AMIRI (Journal of Construction Project Management and Innovation)
A survey was conducted among cyclists in the city of Calgary, Canada, to identify the characteristics of winter cyclists in a metropolitan area with a very cold climate, and to investigate what variables are most likely to affect their cycling behavior. The findings of the survey reveal that even very low temperatures do not appear to be a major concern for most participants. Instead, the majority of cyclists mentioned road surface conditions, rather than the weather itself, to be the major deterrent to winter cycling. In order to analyze the direct and indirect relationships between the different variables affecting winter cycling, a multi layered model was developed. The model distinguishes between the cyclists' inherent characteristics, cycling behavior v ariables and motivating factors that could both affect cycling behavior and be affected by inherent characteristics. Since the cyclists' inherent characteristics, such as age and gender, cannot be changed, identifying and addressing the cyclists' motivatin g factors could be a key to influencing cycling behavior.